Variant logic meta-data management for model driven applications - Davis, Jon; Chang, Elizabeth (SciTePress, 2011)
The scope for end users to influence the design and functionality of off the shelf Enterprise Information system (EIS) applications is usually minimal, requiring pursuing expensive vendor supported customisations. Our ongoing development of temporal meta-data EIS applications seeks to overcome these issues, through modelling rather than coding, and with the meta-data model supporting the capability for end users to define their own application logic meta-data, to supplement or replace the originating vendor’s pre-defined application logic, as what we term Variant Logic. Variant Logic can be applied to any object defined in a meta-data EIS application, and can be defined by any authorised user, without the need for additional coding, and is available for immediate execution by the framework runtime engine. Variant Logic is also preserved during automated meta-data application updates.